Complicated encephalitis in pediatrics: a case report - Santana, Marília Freitas; Ferreira, Lara Moreira; Barbosa, Gabriele Sousa; Souza, Liane Carvalho de Brito de; Jucá, Carlos Eduardo; Filho, Washington Aspilicueta Pinto (Brazilian Journal of Case Reports, 2021)
Encephalitis is a potentially fatal inflammation of the brain parenchyma, of infectious or immunological etiology. This article is a case report of a 9-month-old child who evolved to death, demonstrating the difficulty in making the diagnosis, due to the symptoms of this disease being, in most cases, nonspecific and with several differential diagnoses.